Dominic Cutilletta: capstone - Cutilletta, Dominic, artist (Colorado State University. Libraries, 2022)
The artist's statement: Making things has always been my way of expressing myself, with a physical manifestation, or tangible objects being the result of my understanding and interactions with the world. I am making work that puts me into my own world in which I can do anything I want, and essentially draw in metal in a way that will hold up over time within a 3D space. I think the confrontation sculpture creates with the viewer, often interacting directly with each other is a very powerful and relevant aspect of sculpture that’s helped my body of work land where it is. I’m constantly focused on my emotions resulting from the situations we find ourselves in as humans who form relationships with one another and things around us that can’t be seen, but experienced. The relationships and connections I've formed with the beings and things I've experienced throughout my life is a driving force in preserving memories through sculpture. I've chosen to represent this through metalwork and welding specifically to satisfy my appetite for irony in that it’s one of the processes holding, or connecting much of the world around us together. I want to accentuate and display a material of which I love with formal concepts reminiscent of a creepy whimsical fuzzy dreamscape memory.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture